Urgent adaptive effects of a single intake of carbohydrate-electrolyte mixture with plant extracts in maintaining microcirculation parameters of highly qualified athletes - N.S. Tribrat; S.V. Pogodina; E.A. Biryukova; E.N. Chuyan (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the short-term adaptive effects of a single dose of a carbohydrate-electrolyte mixture with plant antioxidants (CEMA) in maintaining the microcirculation system using the example of highly qualified orienteers under the conditions of a two-stage bicycle ergometric test PWC170. Methods and structure of the study. Highly skilled orienteers aged 17-22 years old were examined. Two cycles of the study were conducted: a placebo cycle in which athletes consumed 250 ml of bottled water; a cycle of taking 250 ml of CEMA. Laser Doppler flowmetry was used as a method for studying microcirculation. Results of the study and their discussion. As a result of the conducted studies of a single dose of CEMA, a vasoprotective effect was established. This effect is due to the restoration of the functional activity of the microvascular endothelium and is expressed in an increase in the amplitude values of endothelial rhythms in the cycle of taking CEMA in comparison with the placebo cycle. Also, a single dose of CEMA contributed to a decrease in the effects of sympathetic adrenergic vasomotors on the vascular wall, which can be considered as a concomitant antihypoxic effect and is expressed in a decrease in lactate levels.